GENDER EDUCATION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN THE CONDITIONS OF BOARDING SCHOOLS - Sultanova, Natalia; Mykhaylyshyn, Galyna; Kondur, Oksana (Mountain School of Ukrainian Carpaty, 2021)
The article highlights the results of the analysis of the state and features of gender education of children with special educational needs in the conditions of boarding schools. The understanding of the essence of gender education from the standpoint of socio-pedagogical science as a purposeful, organized and controlled process of children's assimilation of gender ideas, moral and ethical norms in the relationship of both sexes and the formation of role positions is revealed. The purpose of gender education is actualized and attention is focused on its key tasks in boarding schools, in particular the education of a person capable of mastering his gender role and egalitarian values of modern society. Gender education of students with special needs in the conditions of stay in boarding schools involves the creation of appropriate organizational and pedagogical conditions that will promote the education of a diverse personality, independent, equal regardless of gender. The result of socio-pedagogical activities of boarding schools should be the formation of gender education and culture, sensitivity and tolerance of students in intersex communication, which is manifested in the readiness of boys and girls for adult life in society, marriage and family and professional roles, not burdened with stereotypes.